Using Action Research to Design Bereavement Software: Engaging People with Intellectual Disabilities for Effective Development. Issue 3 (12th April 2013) - Read, Sue; Nte, Sol; Corcoran, Patsy; Stephens, Richard
<x xml:space="preserve">Abstract</x> Background Loss is a universal experience and death is perceived as the ultimate loss. The overarching aim of this research is to produce a qualitative, flexible, interactive, computerised tool to support the facilitation of emotional expressions around loss for people with intellectual disabilities. This paper explores the process of using Participatory Action Research (PAR) to develop this tool. Materials and methods Participator Action Research provided the indicative framework for the process of developing a software tool that is likely to be used in practice. Results People with intellectual disability worked alongside researchers to produce an accessible, flexible piece of software that can facilitate storytelling around loss and bereavement and promote spontaneous expression that can be shared with others. Conclusion This tool has the capacity to enable individuals to capture experiences in a storyboard format; that can be stored; is easily retrievable; can be printed out; and could feasibly be personalised by the insertion of photographs.